T-Cell Receptor Therapy in the Treatment of Ovarian Cancer: A Mini Review - Wu, Jessica W. Y.; Dand, Sudiksha; Doig, Lachlan; Papenfuss, Anthony T.; Scott, Clare L.; Ho, Gwo; Ooi, Joshua D. (Frontiers in Immunology, 2021)
Ovarian cancer, in particularly high-grade serous ovarian cancer (HGSOC) and ovarian carcinosarcoma (OCS), are highly aggressive and deadly female cancers with limited treatment options. These tumors are generally unresponsive to immune check-point inhibitor (ICI) therapy and are referred to as immunologically “cold” tumors. Cell-based therapy, in particular, adoptive T-cell therapy, is an alternative immunotherapy option that has shown great potential, especially chimeric antigen receptor T cell (CAR-T) therapy in the treatment of hematologic malignancies. However, the efficacy of CAR-T therapy in solid tumors has been modest. This review explores the potential of another cell-based therapy, T-cell receptor therapy (TCR-T) as an alternate treatment option for immunological “cold” OC and OCS tumors.